UJI DAYA HAMBAT ANTIBAKTERI SALEP EKSTRAK ETANOL DAUN PANDAN HUTAN (Freycinetia sessiliflora Rizki.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus epidermidis - Fitri Sri Rizki; Ade Ferdinan (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Freycinetia sessiliflora Rizki is a plant that has secondary metabolites, namely alkaloids, flavonoids, terpenoids-steroids, saponins, phenols and tannins. This study aims to determine whether there is inhibitory and concentrated ointment extract of thick pandanus leaf of the forest that can inhibit the growth of Stapylococcus epidermidis bacteria. Inhibition testing was carried out by disk diffusion method with different concentrations of 5% and 10% concentrations made 9 ointment formulas with a variety of 3 bases namely hydrocarbon base, absorbency base and water soluble base. The results of inhibitory measurements of ethanol extract ointment leaves of pandanus leaves are good or have the greatest value to the smallest inhibitory effect on the growth of Staphylococcus epidermidis bacteria with an average diameter of inhibition at F6 of 4.11 mm, F1 of 2.78 mm, F3 of 2.68 mm, F5 of 2.47 mm, F4 of 2.25 mm, F2 of 2.23 mm, F7 of 1.29, F8 of 1.13 and F9 of 0.86 mm.